Analysis of Mercury (Hg) Heavy Metal Content in Rice Snail (Pila ampullacea) Derived from Rawa Taliwang Lake, West Sumbawa Regency - Khairuddin; M. Yamin; Kusmiyati (Jurnal Biologi Tropis, 2023)
Danu Rawa Taliwang is a large body of water that receives sources of heavy metal pollution from human activities such as agriculture and mining. By using bioindicators such as fish, heavy metals have been detected in the waters. The aim of the study was to determine the content of heavy metal mercury (Hg) in the Rice Field Snail (Pila ampullacea) originating from Lake Rawa Taliwang to enrich Ecotoxicology course material. The special benefit is to protect consumers who consume fish from heavy metal contaminants.  Sample Snail was put into a plastic bag and then stored in a sample box. The research sample was then analyzed at the Environmental Laboratory Center for the West Nusa Tenggara Environment and Forestry Office. The method of data analysis was carried out by taking muscle tissue from snails and then analyzing the content of heavy metals in the form of Hg using an Atomic Absorption Spectrophotometer. Heavy metals in snail tissue were measured after adding concentrated HNO3 and HClO4, which were heated at 60-70ºC for 2-3 hours until the solution was clear. Ready samples were measured by AAS using an air-acetylene flame. The conclusion of this study is that the heavy metal content of Hg in rice field snails (Pila ampullacea) originating from Lake Rawa Taliwang to enrich Ecotoxicology course material ranges from 0.96 ppm to 1.91 ppm.